Envelhecimento humano e educação na perspectiva de uma inclusão social - Fernandes, Elizabeth Gomes de Sousa (Universidade Federal do Tocantins, 2021)
The present work discussed the recognition of the importance of aging and the role of education in the perspective of the social inclusion of the elderly. The project characterizes the socio-historical context of the elderly as a subject of rights, as well as identifying and describing the reasons and expectations of the elderly regarding the return to the educational process. Thus, for a better understanding of the theme, a brief basis was made with data from the 1988 Constitution, as well as the Statute of the Elderly, documents that guarantee rights for the elderly. In addition to these, present a brief history of the University of Maturity, its objectives, the Political Pedagogical Project, its historical context, main impacts on society and the elderly, from its application and regulation in the State of Tocantins, and the relevance in promotion of socio-educational activities of its actions and programs, and finally, to investigate the relationship between human aging and education, in the perspective of its social inclusion. Thus, it addresses a relevant socio-political issue, including the elderly as an autonomous subject in society is everyone's obligation.